INFLUENCE OF ADDITIVES ON THE PROPERTIES OF ALIPHATIC ALCOHOLS GASOLINE: ANALYTICAL REVIEW - Бойченко, С. В.; Бойченко, М. С.; Личманенко, О. Г.; Кабан, С. М. (Science-based technologies, 2015)
Development of Aviation has provided almost all modern aircraft fuel systems but without the modified fuel full environmental effects cannot be achieved. Therefore, the development of environmentally friendly alternative aviation fuels based on aliphatic alcohols is extremely important. Given the fact that the published data on the impact of the additives oxygenates aviation gasoline is almost absent. For basic analogue situation was taken modifying the composition of motor gasoline. The main advantages of fuels with higher aliphatic alcohols include Anti-knock characteristics and improved environmental properties. When using alcohol decreases the amount of carbon monoxide, nitrogen oxides and soot, but increases the content of aldehydes in exhaust gas engines. Introduction to motor gasoline oxygenates increases their detonation resistance, as increases the concentration of oxygen in the fuel which enhances the combustion of hydrocarbons, reduces heat of combustion fuel air mixture is more rapid removal of heat from the combustion chamber, resulting in reduced maximum combustion temperature.